PENGARUH PEMAHAMAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN PAJAK PENGHASILAN WAJIB PAJAK UMKM DENGAN PENERAPAN E-FILING SEBAGAI VARIABEL INTERVENING (STUDI PADA KANTOR PELAYANAN PAJAK PRATAMA BOYOLALI) - Putro, Rembranto Gusani; Saryadi, Saryadi (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2019)
Directorate General of Taxes trying to advance taxpayer compliance with tax reform. KPP Pratama Boyolali showed an increasing trend of Annual Tax Retun realization in total, but it was not followed by the level of MSME tax reporting compliance of Annual Tax Return in Boyolali which actually had a decline. In order to examine the problem, a research was executed to determine the effect of taxpayer comprehension and tax penalties towards MSME tax reporting compliance of Annual Tax Return through e-filing implementation as an intervening variable at KPP Pratama Boyolali. This research belong to explanatory research. Sampling technique used by researcher is cluster random sampling method with 148 samples from MSME Taxpayers that are registered at KPP Pratama Boyolali. Data analysis techniques consist of validity test, reliability test, cross tabulation, correlation coefficient, coefficient of determination, simple linear regression, multiple linear regression, t test and F test, and sobel test. The results showed that the taxpayers comprehension and tax penalties partially had a significant effect toward e-filing impelementation, e-filing implementation had a significant effect toward tax reporting compliance of Annual Tax Return, e-filing implementation could mediate between the taxpayers comprehension toward tax reporting compliance of Annual Tax Return, as well as the e-filing implementation could mediate between tax penalties toward tax reporting compliance of Annual Tax Return. The taxpayer comprehension regarding the regulation and tax penalties are expected to make taxpayers to submit their Annual Tax Returns, especially using e-filing applications.